Impact of Human Immunodeficiency Virus Type 1 (HIV-1) Genetic Diversity on Performance of Four Commercial Viral Load Assays: LCx HIV RNA Quantitative, AMPLICOR HIV-1 MONITOR v1.5, VERSANT HIV-1 RNA 3.0, and NucliSens HIV-1 QT - Swanson, Priscilla (American Society for Microbiology (ASM), 2005)
Human immunodeficiency virus type 1 (HIV-1) evolution and changing strain distribution present a challenge to nucleic acid-based assays. Reliable patient monitoring of viral loads requires the detection and accurate quantification of genetically diverse HIV-1. A panel of 97 HIV-1-seropositive plasma samples collected from Cameroon, Brazil, and South Africa was used to compare the performance of four commercially available HIV RNA quantitative tests: Abbott LCx HIV RNA Quantitative assay (LCx), Bayer Versant HIV-1 RNA 3.0 (bDNA), Roche AMPLICOR HIV-1 MONITOR v1.5 (Monitor v1.5), and bioMérieux NucliSens HIV-1 QT (NucliSens). The panel included group M, group O, and recombinant viruses based on sequence analysis of gag p24, pol integrase, and env gp41. The LCx HIV assay quantified viral RNA in 97 (100%) of the samples. In comparison, bDNA, Monitor v1.5, and NucliSens quantified viral RNA in 96.9%, 94.8%, and 88.6% of the samples, respectively. The two group O specimens were quantified only by the LCx HIV assay. Analysis of nucleotide mismatches at the primer/probe binding sites for Monitor v1.5, NucliSens, and LCx assays revealed that performance characteristics reflected differences in the level of genetic conservation within the target regions.